The Myth of Don Juan in Life and Literary Works of Alexander Blok and Valery Bryusov - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
The subject of interest in this article is the myth of Don Juan in the life and literary works of two great figures of the Silver Age – Alexander Blok and Valery Bryusov. The consideration of the biographies of writers (Blok’s marriage to Mendeleeva, Bryusov’s romance with Nina Petrovskaya) as well as selected examples from their literary works (Blok’s poems: “Ya ee pobedil nakonets…”, “The Commander’s Footsteps”; Bryusov’s poems: “I snova…”, “Don-Juan”) in the context of the culture of the Silver Age (the philosophy of Vladimir Solovyov, the idea of ​​life-creation, ideas about the “Eternal Feminine”, the myth of the Beautiful Lady, the vampiric myth) led us to the conclusion that the ‘don juanism’ was one of the important components of the myths of poets. We noted that in both cases the concept of ‘don juanism’ is strictly correlated with the concept of vampirism. On the other hand, it is also related to such concepts as “Eternal Femininity”, ‘true to the ideal’, and ‘the role of art’. All these provide us with the basis to state that the productivity and potential of the theme of Don Juan goes far beyond the usual notion of Don Juan as a seducer.